The US Supplemental Nutrition Assistance Program – Education improves nutrition-related behaviors. (2020) - Ryan-Ibarra, Suzanne; DeLisio, Amy; Bang, Heejung; Adedokun, Omolola; Bhargava, Vibha; Franck, Karen; Funderburk, Katie; Lee, Jung Sun; Parmer, Sondra; Sneed, Christopher
Abstract: The aim of this study was to measure whether participating in Supplemental Nutrition Assistance Program – Education (SNAP-Ed) interventions is associated with changes in meeting recommendations for healthy eating and food resource management behaviours, such as shopping, among low-income children, adolescents, and adults in eight states in the US Southeast. The study used a one-group pre-test post-test design, analysing aggregate data on nutrition and shopping behaviours collected during Federal Fiscal Year 17 from SNAP-Ed direct education in community settings. Twenty-five implementing agencies in Alabama, Florida, Georgia, Kentucky, Mississippi, North Carolina, South Carolina, and Tennessee provided aggregated data on program participants. Because survey questions differed, agencies followed standard recoding guidelines. The number of participants varied depending on the indicator; the maximum number was n 43 303 pre-tests, n 43 256 post-test. Participants were significantly more likely to consume more than one kind of fruit (pooled relative risk (RR), 1⋅10; 95% confidence interval (CI), 1⋅09–1⋅11) and more than one kind of vegetable (pooled RR, 1⋅14; 95% CI, 1⋅12–1⋅15) after the intervention than before. On average, participants consumed 0⋅34 cups more of fruit per day (95% CI, 0⋅31–0⋅37), and 0⋅22 cups more of vegetables per day (95% CI, 0⋅19–0⋅25) after the intervention, compared to before. About 701 policy, systems, and environmental changes for nutrition supports were reported. This study suggests that SNAP-Ed direct education is associated with positive behaviour changes in the US Southeast. It provides a methodology that can inform data aggregation efforts across unique SNAP-Ed programs or other similar nutrition education programs to report on the collective impact.